Occupational Burnout and Productivity Loss: A Cross-Sectional Study Among Academic University Staff - Amer, Shaimaa A. A. M.; Elotla, Sally Fawzy; Ameen, Abeer Elsayed; Shah, Jaffer; Fouad, Ahmed Mahmoud (Frontiers in Public Health, 2022)
Background Burnout has been endorsed with serious negative health- and work-related outcomes. This study is aimed to assess the prevalence of burnout and its association with work productivity among academic staff. Methods This cross-sectional study involved 240 academic staff working at a public university in Egypt. Participants were invited to complete a web-based questionnaire involving basic personal, health, and work-related characteristics. Besides, Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was used to assess occupational burnout dimensions (i.e., emotional exhaustion “EE,” depersonalization “DP,” and personal accomplishment “PA”), while work productivity was assessed with the Health and Work Performance Questionnaire (HPQ). Results In total, 28% of respondents scored high in EE [95% confidence interval (CI): 22.5–33.8%], 18.3% high in DP (95% CI: 13.8–3.6%), and 88.3% scored low in PA (95% CI: 83.8–91.9%). Seventy percent of respondents scored high in only one burnout dimension, 21.7% scored high in two dimensions, while 7.1% scored high in all three dimensions. Multivariable analysis showed that EE was the only burnout dimension that showed a statistically significant association between absenteeism and presenteeism rates. The absenteeism rates among respondents with moderate and high EE were 2.1 and 3.3 times the rates among those with low EE, respectively. Likewise, the presenteeism rates among respondents with moderate and high EE were 2.4 and 4.7 times the rates among those with low EE, respectively. Conclusions Academic staff showed a high prevalence of at least one burnout dimension. Moderate and high EE scores were significantly associated with increased productivity loss when compared to low EE.